Is the past the prologue for the future of agricultural in the United States? - Glauber, Joseph W.; Smith, Vincent H. (American Enterprise Institute, 2021)
Key Points Over the past 20 years, Congress has substantially increased federal crop insurance subsidies and shifted direct payments to farmers away from payments decoupled from current prices and yields toward countercyclical payments. Ad hoc disaster relief payments to farmers ballooned in recent years in response to trade disputes with China and the coronavirus pandemic, arguably outweighing farm losses, but these subsidies may not continue. The Joe Biden administration is promoting initiatives to increase subsidies received by minorities and small family farmers and expand funding for conservation and greenhouse gas emission–reduction practices on farms.